Perancangan Sistem Informasi Kearsipan Berbasis Website Pada Kantor Pencarian Dan Pertolongan Kelas A Medan - Olivia Maylina; Fauziah Decfina; Heri Santoso (Journal Of Informatics And Busisnes, 2024)
The Medan Class A Search and Rescue Office is a technical implementation unit tasked with carrying out search and rescue (SAR) operations in the North Sumatra region. In the Medan Class A Search and Rescue Office, the relationship between budgets and documents is closely related because documents are often used as a tool to record, track and present information. These documents assist the Medan Class A Search and Rescue Office in monitoring, evaluating and making decisions related to search and rescue operations. The document is an important reference to ensure transparency, accountability and efficiency of budget management in accordance with policies and community needs. The existence of documents is usually important because they record or record information that can be accessed and used as a reference in the future. Document management within the Medan Class A Search and Rescue Office still faces several obstacles, including manual processes that are vulnerable to human error, the time required to search for documents, and the risk of loss or damage to documents. Seeing this problem, a new system is needed that utilizes technology in the current era to deal with several obstacles related to document management. The aim is to design and implement a web-based document archiving information system at the Medan Class A Search and Rescue Office to increase efficiency, security and readability of information in document management. This system was built by modeling several UML diagrams such as use case diagrams and activity diagrams. It is hoped that the Medan Class A Search and Rescue Office can optimize document management performance and make a positive contribution to improving service quality and transparency within government agencies.